Business Process Reengineering and Cost Benefit Analysis: Case Study on Tax Penalty Avoidance at ConocoPhillips Indonesia Inc. - , Eko Purnama Jaya; , Dr.Erni Ekawati MBA., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
With the issuance of Ministry of Finance Regulation Number 11 Year 2005 (MoFR-11/2005) regarding VAT Collector, the Production Sharing Contract (PSC) Contractors in Oil and Gas Industry in Indonesia face a new challenge. They are confronted with operational constrain to adapt to the regulation. In addition, difficulties to apply the regulation lead to raise serious financial impact through the issuance of tax penalty. This study examine constrains and problems of ConocoPhillips Inc. as representative of PSC contractors, and to propose a tax avoidance solution with Business Process Reengineering initiative and examine it in Cost Benefit Analysis perspective. Tax penalty avoidance solution is carried out by crafting the reengineering proposal that is outlaid in reengineering plan. Reengineering plan is a tactical plan consisting check points. From each check points, there will be solid step to execute. Check point and each steps inside is an integration of reengineering plan a la McKinsey and BCG. After reengineering plan defined, then cost for the project is also estimated. From the cost estimation and cost saving potential, the numbers will be projected and the Net Present Value (NPV) will be calculated. The NPV obtained is Rp. 120,7 billion or US$ 14,03 million. Meanwhile, business process reengineering can potentially offer Benefit/Cost Ratio of 40,58 and cost saving of 396% per year then the reengineering proposal is feasible to execute.